1988
DOI: 10.1111/j.2042-7158.1988.tb06308.x
|View full text |Cite
|
Sign up to set email alerts
|

High speed photographic analysis of aerosols produced by metered dose inhalers

Abstract: The design of pressurized metered dose inhalers (MDI) used to assess asthma is variable. We have examined the aerosol spray flumes generated by four commercially available MDI products using high speed video photography. For this purpose a moulded jacket was designed which could hold the inhaler in an immovable position during actuation. Fresh inhalers were fitted in the jacket after thorough shaking and three successive actuations 30 s apart were filmed with a high speed video camera (200 frames s-1). The aer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

1990
1990
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 3 publications
1
14
0
1
Order By: Relevance
“…The aerosol produced by the Ventolin® MDI was moving faster than that produced by the Airomir® MDI. Others have also measured the speed of aerosols from MDIs [15], producing results similar to those of the present study for a Ventolin® MDI. Particles from the Ventolin® MDI would have reached the end of the Aerochamber® (11 cm length) some 8 ms after MDI actuation, compared with 23 ms for Airomir®.…”
Section: Discussionsupporting
confidence: 79%
“…The aerosol produced by the Ventolin® MDI was moving faster than that produced by the Airomir® MDI. Others have also measured the speed of aerosols from MDIs [15], producing results similar to those of the present study for a Ventolin® MDI. Particles from the Ventolin® MDI would have reached the end of the Aerochamber® (11 cm length) some 8 ms after MDI actuation, compared with 23 ms for Airomir®.…”
Section: Discussionsupporting
confidence: 79%
“…This time, a large prototype was used as spacer device. The dimensions of the prototype were chosen based on a high-speed photographic analysis of the pMDI cloud (22). The results shown in Table 2 confirmed the prediction of an inhaled mass quantity similar to the amount obtained with heated and dry air with the Aerochamber (see Table 1, 37Њ C and RH ϭ 8%).…”
Section: Spacer Design Revisitedmentioning
confidence: 80%
“…Dhand et al (1988) suggested a high-speed video recording method to analyze the aerosol velocity, * Corresponding author. Tel.…”
Section: Introductionmentioning
confidence: 99%